Rigid crosslinker-assisted nondestructive direct photolithograph for patterned QLED displays - Chen, Zhong; Man, Zhongwei; Rao, Shichao; Zhao, Jinxing; Wang, Shuaibing; Zhang, Runtong; Teng, Feng; Tang, Aiwei (Light, science & applications, 2025)
Recently, colloidal quantum dots (QDs) with high luminescent efficiency and tunable colors have become ideal materials for next-generation display devices. Direct photolithography is a powerful tool for patterning QD devices, but it faces the serious issue of degradation in the photophysical properties of the patterned QDs. Here, we use relatively rigid cyclopentane as a bridging group to design the crosslinker CPTA, achieving high-resolution direct photolithography of QDs with nearly nondestructive under ambient conditions. The key to the crosslinker design is the introduction of a rigid bridging group that elevates the LUMO level, providing a stronger energy barrier to prevent QD electrons from being trapped or undergoing non-radiative recombination, thus preserving their PL and EL properties. The efficient and high-resolution RGB line and dot arrays were fabricated with pixel sizes down to 1 μm and a resolution of up to 6350 PPI. The patterned RGB QD films, especially red QDs, maintained their optical and optoelectronic properties, with patterned red QLEDs achieving peak external quantum efficiency (EQE) of 21% and a maximum luminance ( L max ) of ~180,000 cd m⁻², matching pristine devices. These results highlight the importance of photo-crosslinker design for nondestructive QDs patterning, paving the way for advanced display applications in patterned QLED technology. This work innovatively designed a rigid high-LUMO bridging photo-crosslinker for nondestructive high-resolution QD patterns with a resolution of 6350 PPI, and high-performance QLED displays with EQE of 21%.